2006
DOI: 10.1021/jp062003p
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin Cavity Size Effect on the Complexation and Rotational Dynamics of the Laser Dye 2,5-Diphenyl-1,3,4-oxadiazole:  From Singly Occupied Complexes to Their Nanotubular Self-Assemblies

Abstract: The general complexation scheme as well as the dynamic features of the supramolecular structures resulting from the interaction of the laser dye 2,5-diphenyl-1,3,4-oxadiazole (PPD) with the naturally occurring alpha-, beta-, and gamma-cyclodextrins in water are studied by means of fluorescence spectroscopy, both steady-state (SS) and time-resolved (TR). PPD interacts weakly, from a thermodynamic point of view, with alpha-cyclodextrin (alpha-CD), forming 1:1 complexes with an association constant of K(11) = 85 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…No aggregation phenomena were observed in a good solvent such as tetrachloroethane at ambient temperatures, as demonstrated by time-resolved fluorescence depolarization spectroscopy in conjunction with the Stokes−Einstein−Debye (SED) equation. By applying the spherical rotor anisotropy model to the experimental I VV and I VH data of 3 at 23 °C, the rotational reorientation time τ r of 3 (0.70 μM) was determined to be 655 ± 40 ps (Figure and SI). This experimental value corresponds to a rotating spheroid with a molecular volume of ∼1690 Å 3 which is in accordance, within experimental error, with the one calculated from the monomeric unit of the X-ray crystal structure of 3 (∼1780 Å 3 including van der Waals radii).…”
mentioning
confidence: 99%
“…No aggregation phenomena were observed in a good solvent such as tetrachloroethane at ambient temperatures, as demonstrated by time-resolved fluorescence depolarization spectroscopy in conjunction with the Stokes−Einstein−Debye (SED) equation. By applying the spherical rotor anisotropy model to the experimental I VV and I VH data of 3 at 23 °C, the rotational reorientation time τ r of 3 (0.70 μM) was determined to be 655 ± 40 ps (Figure and SI). This experimental value corresponds to a rotating spheroid with a molecular volume of ∼1690 Å 3 which is in accordance, within experimental error, with the one calculated from the monomeric unit of the X-ray crystal structure of 3 (∼1780 Å 3 including van der Waals radii).…”
mentioning
confidence: 99%
“…Once the nucleus M 2 is formed, the development of aggregates is modeled to proceed in a similar fashion as the K 2 – K model predicts, i.e., by the successive addition of the active unit M 1 to the growing self-assembled aggregate, , i.e., isodesmically, each step of which ( n ⩾ 3) preserves the same association constant ( K A ), as shown in Scheme and described by the equations given in the Supporting Information. In fact, as shown in Scheme , subsequent attachment of monomeric units (mauve-colored M 1 ) along the direction perpendicular to the mean plane of PBIs ( a axis) is favored by the concerted action of ionic (core of S ) and π–π or C–H ···· π interactions (terminal PBIs of S ), providing collectively the driving force for building up the PBI columnar direction.…”
Section: Resultsmentioning
confidence: 99%
“…1. Previous efforts have indicated that various forms of CD are effective in forming inclusion complexes with molecules that incorporate the 1,3,4-oxadiazole ring, [37][38][39] while carbazole-containing molecules have been the focus of a number of studies on the alteration of its luminance characteristics with inclusion in CDs. [40][41][42][43][44][45] The far right image in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This relative affinity to water and the influence of b-CD in incorporating AD1 and AD2 was confirmed by a preliminary fluorescence analysis of the b-CD:AD1 and b-CD:AD2 inclusion complexes; b-CD is less effective in raising the concentration of AD2 in an aqueous solution relative to AD1. The creation of supramolecular architectures between the b-CD and the oxadiazole 38 and dyes, 48 coupled with both an enhanced availability and reactivity at the transformation site, 49-51 may account for their higher grafting densities on the PA particles.…”
Section: Elemental and X-ray Photoelectron Spectroscopy (Xps) Analysismentioning
confidence: 99%